The importance of project management in the implementation of environmental management systems in companies: A literature review - Rebello, Flávia Adriana Santos; Lima, Lucas Alves de Oliveira; Filho, Teodoro Antunes Gomes; Perera, Allan Berthier Silva; Manca, Ricardo da Silva; Lessa, Mikhael Buzon; Guimarães, Deliane Andrade; Sousa, Weverton Wylar Silva de; Pozeti, Gabriela Eloísa de Oliveira; Junior, Antonio Pereira da Silva (Seven Editora, 2024)
The objective of this research was to analyze the importance of project management in the implementation of environmental management systems in companies through a literature review. Based on the literature search, it was found that project management plays an essential role in the implementation of environmental management systems in organizations. The structured and systematic approach provided by project management allows for proper planning, controlled execution and continuous monitoring of activities related to environmental management. This includes clearly defining objectives, analyzing tasks, allocating resources appropriately, coordinating stakeholders, and evaluating the results achieved. By adopting project management as an integral part of the implementation of environmental management systems, organizations are more likely to achieve success and significant benefits, such as reduced environmental impacts, compliance with regulations, and a better reputation in the market. These practices not only demonstrate the commitment to sustainability and social and environmental responsibility, but also strengthen the image of organizations in the eyes of customers, investors, and society as a whole. DOI:https://doi.org/10.56238/sevened2024.007-012